2000
DOI: 10.1016/s0092-8674(00)00073-8
|View full text |Cite
|
Sign up to set email alerts
|

p53AIP1, a Potential Mediator of p53-Dependent Apoptosis, and Its Regulation by Ser-46-Phosphorylated p53

Abstract: Through direct cloning of p53 binding sequences from human genomic DNA, we have isolated a novel gene, designated p53AIP1 (p53-regulated Apoptosis-Inducing Protein 1), whose expression is inducible by wild-type p53. Ectopically expressed p53AIP1, which is localized within mitochondria, leads to apoptotic cell death through dissipation of mitochondrial A(psi)m. We have found that upon severe DNA damage, Ser-46 on p53 is phosphorylated and apoptosis is induced. In addition, substitution of Ser-46 inhibits the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
905
2
7

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,088 publications
(962 citation statements)
references
References 39 publications
48
905
2
7
Order By: Relevance
“…In addition, transgelin interacts with p53 upregulating and stabilizing it (Figures 2A and 4). Phosphorylation of p53 at Ser46 is considered to be a primary determinant for the induction of apoptosis, by leading to selective transactivation of p53 target genes that have proapoptotic function [39]. We found that the introduction of transgelin results in the upregulation of phospho-p53 Ser46, which can induce apoptosis.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, transgelin interacts with p53 upregulating and stabilizing it (Figures 2A and 4). Phosphorylation of p53 at Ser46 is considered to be a primary determinant for the induction of apoptosis, by leading to selective transactivation of p53 target genes that have proapoptotic function [39]. We found that the introduction of transgelin results in the upregulation of phospho-p53 Ser46, which can induce apoptosis.…”
Section: Discussionmentioning
confidence: 78%
“…M, molecular weight marker; WT, wild type (p53 + / + ); N, nonischemic wild-type mice; 12 h, 12 h after ischemia; 24 h, 24 h after ischemia. p53 potentiates ischemic neuronal death I Yonekura et al ischemic stress may modify the protein into several active forms by phosphorylation, leading to a conformational change (Fuchs et al, 1995;Oda et al, 2000b;Koumenis et al, 2001;Latonen et al, 2001). Using antibodies against p53 phosphorylated at serines 18, 23, 37, 312, and 392 (kind gift from Dr Taya), we could not identify these forms (data not shown).…”
Section: Discussionmentioning
confidence: 91%
“…For example, JNK has been proposed to modulate the release of pro-apoptotic factors from the mitochondrion (Fig. 5) and stabilizes the pro-apoptotic p53, which in term may impairs mitochondrial functions thorough the expression of p53AIP1 and a subsequent permeability transition [144]. On the contrary p53 might activate JNK via the MEKK4 involving the p53-mediated expression of the growth arrest and DNA damage-induced protein (GADD45) [201].…”
Section: Apoptosis Mitochondrial Function and Mapk Signal Transductionmentioning
confidence: 99%